Teacher Collaboration in Integrative Curriculum Development at Nature-Based Schools - Ilmiati Ikhtiari Susamsa; Mada Sutapa (Journal of Education and Teaching Learning, 2026)
Nature-based schools have grown rapidly worldwide, yet research on how teachers collaborate to develop integrative curricula within these settings—and what ecosystem factors shape such collaboration—remains limited. This study aimed to systematically synthesise existing literature on teacher collaboration in integrative curriculum development at nature-based schools, identify enabling and impeding ecosystem factors, and map current research gaps. A Systematic Literature Review (SLR) following the PRISMA protocol was conducted, screening 90 articles from four databases (ERIC, Google Scholar, Scispace, and Semantic Scholar) published between 2015 and 2026, from which 43 articles met all inclusion criteria. Thematic analysis revealed four main forms of teacher collaboration: curriculum co-planning and co-design, interdisciplinary team teaching, professional learning communities (PLC), and collaboration with external actors. Four ecosystem factor categories were identified as enablers and barriers: school leadership (the most determinant factor), school culture, educational policy, and the physical-community ecosystem of nature-based schools. Five critical research gaps were identified, notably the scarcity of studies in Asian and Indonesian contexts, the absence of integrative research simultaneously examining all three variables, and the lack of longitudinal studies. These findings indicate that effective teacher collaboration in nature-based schools requires distributed principal leadership, autonomy-supporting policies, and a systemic collaborative culture, with implications for school principals, policymakers, and researchers.